Ukuran perusahaan dan leverage terhadap nilai perusahaan di Bursa Efek Indonesia: Return on equity sebagai variabel moderasi - Amalina, Nur; Insani, Kharisma Aulia (Nur Science Institute, 2023)
This study examines the effect of firm size and leverage on firm value, with return on equity as a moderating variable. The data used in this study is secondary data from the financial reports of companies listed on the Indonesian Stock Exchange for 2015–2019, using purposive sampling. The analytical method used in this study is moderate regression analysis (MRA). The study results show that firm size, debt-to-equity ratio, and return on equity simultaneously affect firm value. Partially, firm size and the debt-to-equity ratio do not affect firm value. Return on equity has a partial effect on firm value. Return on equity can interact between firm size and firm value but cannot interact between debt-to-equity ratio and firm value. R square in this study is 39.7%, which shows that company size, debt-to-equity ratio, and return on equity contribute 39.7% to firm value.